(untitled) (Bioscience Journal, 2017)
The Neon-S method has been used for detection of Sclerotinia sclerotiorum on soybean and common bean seeds since the 2010 crop season. However, this method can lead to identification of false-positives due to the presence of other fungi that change the medium pH. Thus, this study evaluated the effect of increasing incubation period on the reliability of Neon-S test in detecting S. sclerotiorum infection on soybean and common bean seeds. A randomized block design was set up with three replicates in a 3x3 factorial scheme, consisting of three detection methods (germination paper test, Neon-S, and modified Neon-S2) and three seed material (naturally infected common beans, naturally infected and artificially inoculated soybean seeds). The three methods were compared by evaluating 400 seeds per replication, after incubating them for seven days in Neon-S, for 15 days in Neon-S2, and for 30 days in germination paper, determining the presence of the fungus and of sclerotia adhered to the seeds. The data were submitted to the analysis of variance and the averages compared by the Tukey test at 5% probability. From 2008 to 2012, 637 lots were evaluated. Among the seed material, artificially inoculated soybean presented the greatest pathogen infection index. The germination paper test led to 2.8% of positive samples, contrasting 29.7% of Neon-S. The modified method Neon-S2 increased detection sensitivity of S. sclerotiorum in seed lots (31.2%); however, did not significantly differ from the Neon-S method, despite its greater averages. We concluded that detection of S. sclerotiorum by the Neon-S method can be optimized by incubation for 15 days (Neon-S2), due to the formation of sclerotia near the infect seeds which confirms the presence of the pathogen avoiding false-positive results.